'L'âme générale d'une assemblée': a neglected parliamentarian and the restoration theory of representation. (2nd November 2021) - Conti, Greg
ABSTRACT: The Restoration remains an underserved era in the historiography of French political thought, particularly in scholarship focused on liberalism and representation. This article begins to remedy that deficit by reconstructing and contextualizing the views of a forgotten liberal theorist of representation, Pierre-François Flaugergues, who published two tracts on the subject in the electoral-reform controversies of 1820. Flaugergues is revealed to have been a thinker of force and originality, who advocated an electoral system anchored in class-based constituencies. Not only did Flaugergues ground his preferred representative arrangements in the first principles of moral psychology and natural right, but he linked his proposed scheme to a rich realm of values including deliberation, inclusivity, corporate agency, and stability. While Flaugergues's ideas of representation did not find much of a following in France, he can be understood as participating in a broader liberal tradition of thinking about the purpose and design of representative institutions.